Gender Differences in Career Decision-making Self-Efficacy - Nasiyati, Nur; Sugiyo, Sugiyo; Sunawan, Sunawan (Jurnal Bimbingan Konseling, 2022)
High school students are at a crucial phase because they will experience the transition from school to college or work, requiring them to have the ability to make career decisions. Regarding this issue, the present study aimed to determine gender differences in career decision-making self-efficacy in grade twelve students at SMA Negeri 1 Gringsing, Batang Regency. It used a quantitative approach with a descriptive-comparative design. In terms of sample, the study involved 246 students selected using purposive sampling technique. The students career decision-making self-efficacy data were collected using the career decision-making self-efficacy scale and analyzed using the independent sample t-test. Findings revealed that there was no difference in career decision-making self-efficacy in terms of gender in general. However, the differences were found in the 2 subscales, namely occupational information and problem solving. Thus, it is concluded that female students are more concerned with career issues. The implications of this study are counselors are expected to be able to provide career counseling services to increase career decision-making self-efficacy, especially for male students because the career decision-making self-efficacy of them was lower than female students.